Geo-spatial site suitability analysis for development of health care units in rural India: Effects on habitation accessibility, facility utilization and zonal equity in facility distribution. (June 2019) - Mishra, Sushreeta; Sahu, Prasanta K.; Sarkar, Ashoke K.; Mehran, Babak; Sharma, Satish
Abstract: The development of health care facilities in a nation improves the quality of life of its citizens, and enhances their efficiency and productivity; eventually, reducing poverty. This paper proposed a methodology that uses GIS and multi-criteria decision-making technique for development of health care units (HCUs), to attain spatial efficiency in the distribution of facilities. The methodology assigns spatial weightage to the suitability index of the candidate locations in the objective function of maximizing coverage location-allocation problem embedded in ArcGIS. Habitations unserved by the existing HCUs are considered as candidate locations. The five criteria considered to determine the suitability index of a location are: Access distance to nearest existing HCU (C 1 ), Accessibility index of habitations to existing HCUs based on service to population ratio (C 2 ), Connectivity to all-weather roads (C 3 ), Population of neighborhood (C 4 ), and Health care requirement of a zone (C 5 ) . The proposed methodology is applied in Jhunjhunu district, India as a case study, for the development of Community Health Centers (CHCs). Accessibility of habitation to facilities (jointly C 1, C 2, and C 4 ) found to be the most influencing criteria in deciding the suitability of a candidate location to site the CHCs. The proposed methodology enables maximization of coverage, minimization of needless competition within CHCs, and satisfaction of the zonal requirement for health. Study findings would be helpful to national policymakers for developing HCUs by prioritizing fund allocation to shortage areas to improve the health index as well as the quality of life. Highlights: A generic practice ready methodology is proposed to develop healthcare units in rural area GIS and Multi-criteria technique are used concurrently for location-allocation Spatial weightage is assigned to the suitability index of the candidate location in MCLP Proposed methodology ensures spatial efficiency in the distribution of facilities Findings would help policy makers for fund allocation to improve quality of life